That touch of mink [videorecording (DVD)] - Mann, Delbert, 1920-2007; Grant, Cary, 1904-1986; Day, Doris, 1922-2019-; Young, Gig, 1913-1978; Meadows, Audrey (Olive Films, 2013)
Love arrives with a splash when a handsome, eligible tycoon and a beautiful working woman meet over a rain puddle. He's enchanted by her small town ways, and she's captivated by his romantic, debonair manner. But when it comes to marriage they have decidedly different views, she wants it and he doesn't! It's a game of cat-and-mouse as each tries to win the other, with hilarious and heartwarming results.